Efficacy of Organic Soil Amendments for Management of Heterodera glycines in Greenhouse Experiments - Grabau, Zane J. (The Society of Nematologists, 2014)
In a repeated greenhouse experiment, organic soil amendments were screened for effects on population density of soybean cyst nematode (SCN), Heterodera glycines, and soybean growth. Ten amendments at various rates were tested: fresh plant material of field pennycress, marigold, spring camelina, and Cuphea; condensed distiller’s solubles (CDS), ash of combusted CDS, ash of combusted turkey manure (TMA), marigold powder, canola meal, and pennycress seed powder. Soybeans were grown for 70 d in field soil with amendments and SCN eggs incorporated at planting. At 40 d after planting (DAP), many amendments reduced SCN egg population density, but some also reduced plant height. Cuphea plant at application rate of 2.9% (amendment:soil, w:w, same below), marigold plant at 2.9%, pennycress seed powder at 0.5%, canola meal at 1%, and CDS at 4.3% were effective against SCN with population reductions of 35.2%, 46.6%, 46.7%, 73.2%, and 73.3% compared with control, respectively. For Experiment 1 at 70 DAP, canola meal at 1% and pennycress seed powder at 0.5% reduced SCN population density 70% and 54%, respectively. CDS at 4.3%, ash of CDS at 0.2%, and TMA at 1% increased dry plant mass whereas CDS at 4.3% and pennycress seed powder at 0.1% reduced plant height. For Experiment 2 at 70 DAP, amendments did not affect SCN population nor plant growth. In summary, some amendments were effective for SCN management, but phytoxicity was a concern.